Guidelines Formulation, Appraisal and Approval of Public Private Partnership Projects - Planning Commission (Planning Commission, 2006)
These Guidelines articulate the need for ‘due diligence’ in the formulation, appraisal and approval of Public Private Partnership (PPP) projects of the Central Government. Unlike private projects where prices arc generally determined competitively and Government resources arc not involved. PPP infrastructure projects typically involve transfer of public assets, delegation of governmental authority for recovery of user charges, private control of monopolistic services and sharing of risks and contingent liabilities by the Government. Protection of user interests and the need to secure value for public money, as such, demand a more rigorous treatment of these projects.
Planning Commission Government of India
Planning Commission Government of India